2013
DOI: 10.1007/s00213-013-2983-2
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine derived from the electronic cigarette improves time-based prospective memory in abstinent smokers

Abstract: Rationale: It is well-established that nicotine improves, and deprivation impairs, cognitive performance and mood in smokers. Prospective memory (PM), remembering to execute a delayed intention at a given time point, is under-explored in smokers. Whilst a handful of studies have shown improved PM with nicotine, effects of nicotine delivered via the electronic cigarette have not been investigated.Objective: This study explores whether, by comparison with placebo, nicotine delivered via the e-cigarette can impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 58 publications
2
54
2
1
Order By: Relevance
“…Interestingly, this reduction in desire to smoke or lessening of cravings occurred even in some cases where objectively measured nicotine uptake was low or modest 53 56. Evidence for the alleviation of specific withdrawal symptoms in these lab studies was inconsistent 53 56 57 79 87 88…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, this reduction in desire to smoke or lessening of cravings occurred even in some cases where objectively measured nicotine uptake was low or modest 53 56. Evidence for the alleviation of specific withdrawal symptoms in these lab studies was inconsistent 53 56 57 79 87 88…”
Section: Resultsmentioning
confidence: 96%
“…In six lab studies, participants who had been tobacco abstinent for 2–12 h reported that using nicotine-containing ENDS reduced their desire to smoke or cravings during their inlaboratory use session,53 56 57 79 87 88 although this was not true in one study 54. In some cases, this reduction was shown to be greater for nicotine-containing ENDS than for non-nicotine ENDS53 87 88 or for just holding unlit regular cigarettes or ENDS 56 88. Interestingly, this reduction in desire to smoke or lessening of cravings occurred even in some cases where objectively measured nicotine uptake was low or modest 53 56.…”
Section: Resultsmentioning
confidence: 99%
“…Dawkins et al 34 examined the subjective effects of acute administration of an 18 mg or 0 mg cigarette-like disposable e-cigarette after overnight abstinence in two counterbalanced sessions in a clinical laboratory study involving regular e-cigarette users (n=20). At the end of the 60 min ad libitum smoking period, urge to smoke and anxiety were significantly decreased with the 18 mg e-cigarette.…”
Section: Resultsmentioning
confidence: 99%
“…From tests conducted in the laboratory, we know that craving for tobacco cigarettes decreases immediately after e-cigarette use (Adriaens et al, 2014;Bullen et al, 2010;Dawkins and Corcoran, 2014;Dawkins et al, 2013aDawkins et al, , 2012Evans and Hoffman, 2014;Nides et al, 2014;Vansickel et al, 2010), that nicotine-containing e-cigarettes have a stronger effect on desire to smoke than nicotinefree e-cigarettes (Dawkins et al, 2012), and that being told that the an e-cigarette contains nicotine (even though it actually contains no nicotine) attenuates craving for tobacco (Copp et al, 2014). One study found that new e-cigarette models (refillable tanks) are more effective at relieving craving for tobacco than older models ("cig-alike"; Farsalinos et al, 2014b), but another study found no difference .…”
Section: Introductionmentioning
confidence: 99%